History of Libraries of the Western World - Harris, Michael H. (Rowman & Littlefield Publishers, 1999)
This edition of the History of Libraries in the Western World represents a substantial revision of the earlier edition, taking into account the "information revolution" that has swept the West since 1945 and the political revolution that swept across Europe beginning in 1986. In addition, recent scholarship has been incorporated throughout the text, with special emphasis on the work centered around the "new history of the book." The bibliographies at the end of each of the twelve chapters have been thoroughly revised to reflect the very considerable new work on library and book history.